First record of Eptesicus furinalis (Chiroptera, Vespertilionidae) from the state of Maranhão, Brazil - Cleison Luis da Silva Costa; Ana Priscila Medeiros Olimpío2; Amanda Cristiny da Silva Lima; Samira Brito Mendes; Marcelo Cardoso da Silva Ventura; Elmary da Costa Fraga5,; Maria Claudene Barros (Caldasia, 2022)
A specimen of Eptesicus furinaliswas collected in the municipality of Cândido Mendes, in the state of Maranhão, Brazil. It was a non-lactating adult female, with dark chestnut dorsal coloration, yellow venter, hairless membranes, short and rounded ears, and a pointed tragus. The analysis of the DNA barcode of the COI mitochondrial gene revealed a 99.80 % similarity with the sequence of E. furinalisdeposited in the BOLDSystems platform. The combined analysis of the morphological and molecular data confirmed the occurrence of E. furinalis in the state of Maranhão. This extends the known distri-bution of the species 676.1 km from the nearest recorded locality in the Ceará State.